MODELO DE NEGOCIAÇÃO E O AGENTE MEDIADOR NO AMBIENTE ICS DE COMÉRCIO ELETRÔNICO - Martins, Sérgio Gomes (2007)
This work is part of the ICS Project (Intelligent Commerce System), currently in development in the Intelligent Systems Laboratory (LSI), at Universidade Federal do Maranhão (UFMA), under the coordination of the Prof. Dr. Sofiane Labidi. The project aims at developing an Intelligent environment of negotiation for electronic commerce among companies (business-to-business) and in a approaching in cycle of life composed of five stages. This work aims at main feature of the ICS that is the automation of the negotiation process to provide companies with favorable conditions for commercialization at a low operational cost, with rapidity and efficiency. The negotiation is the stage where the intelligent agents who represent the users (companies), initiate its searches for the satisfaction of its necessities through exchanges of purchase or seller proposals of goods and services. We present the proposed Negotiation Model and a prototype of the mediator agent which is responsible for the management of the negotiation process as a whole.